2012
DOI: 10.5539/ies.v5n5p141
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effectiveness of Vocabulary Learning Strategies on Iranian EFL Learners’ Vocabulary Test Score

Abstract: This study aims to investigate the effectiveness of vocabulary learning strategies on Iranian EFL learners' vocabulary test score. To achieve this aim, fifty Intermediate level students from Kish English Institute were randomly selected from among fifteen classes after administering the Oxford Placement Test (OPT). Then, an intermediate level vocabulary test of 20 questions based on their class textbook named Total English was given to them. A questionnaire of vocabulary learning strategies (VLSQ) was, then, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Matching words with their synonyms yielded a mean score of 7.900, which is also relatively low compared with the three previously mentioned skills. These findings are consistent with Rahimy and Shams's (2012) study, which revealed a significant effect of vocabulary learning strategies on EFL learners' performance in a vocabulary.…”
Section: Discussionsupporting
confidence: 92%
“…Matching words with their synonyms yielded a mean score of 7.900, which is also relatively low compared with the three previously mentioned skills. These findings are consistent with Rahimy and Shams's (2012) study, which revealed a significant effect of vocabulary learning strategies on EFL learners' performance in a vocabulary.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the main concern of Ostovar-Namaghi's MA thesis (2013) was to investigate the effect of strategy training on the vocabulary development of EFL Learners in public high schools of Iran. Similar to the conclusion drawn by Rahimy and Shams (2012), the results were better for the group that got vocabulary strategy training over the group that learned vocabulary through prescribed by textbook activities Interestingly, the current study's findings reveal the connection between the mode of teaching and the students' use of LLSs. The data from the second and third questions show that students in the explicitly trained group used memory and cognitive strategies more than the trained one.…”
Section: Discussionsupporting
confidence: 84%
“…The results revealed that learners' proficiency level affected their application of vocabulary learning strategies and their performance on vocabulary size test. Finally, similar research showed that vocabulary learning strategies had a significant effect on the learners' scores obtained from the vocabulary tests (Rahimy & Shams, 2012).…”
Section: 30mentioning
confidence: 78%